Effect of Temperature of 1.23% Acidulated Phosphate Fluoride Gel on Enamel Microhardness of Permanent Teeth - Shabnam Milani; Mehdi Shahrabi; Nazanin M-Abdi (International Journal of Dentistry)
Conclusion: Increasing the temperature of 1.23% APF gel from 4 to 25°C and 37°C did not cause a significant change in enamel microhardness of permanent teeth.